2023
DOI: 10.3389/fpsyg.2023.1107839
|View full text |Cite
|
Sign up to set email alerts
|

Influence of letter shape on readers’ emotional experience, reading fluency, and text comprehension and memorisation

Abstract: IntroductionThe amount of educational material delivered to pupils and students through digital screens is increasing. This method of delivering educational materials has become even more prevalent during the COVID-19 pandemic. To be as effective as possible, educational material must be properly designed not only in terms of content, but also in terms of form, e.g., the typeface. The present study investigated the effect of letter shape on readers’ feelings of pleasantness during reading, reading fluency, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 78 publications
(77 reference statements)
0
0
0
Order By: Relevance
“…It is important to recognize that the effect of digital materials on learning can vary depending on their mode of use. Reasonable and balanced use of digital materials in the flipped classroom approach can be beneficial for students' learning process (Medved et al, 2023), as demonstrated in this study. Digital materials can offer advantages such as interactivity, access to content-rich resources, and the ability to personalize learning based on individual student needs (Förster et al, 2022).…”
Section: Discussionmentioning
confidence: 64%
“…It is important to recognize that the effect of digital materials on learning can vary depending on their mode of use. Reasonable and balanced use of digital materials in the flipped classroom approach can be beneficial for students' learning process (Medved et al, 2023), as demonstrated in this study. Digital materials can offer advantages such as interactivity, access to content-rich resources, and the ability to personalize learning based on individual student needs (Förster et al, 2022).…”
Section: Discussionmentioning
confidence: 64%
“…However, for a passage-reading task, Katzir and colleagues [47] found that decreasing font size yielded lower reading comprehension scores in 2nd graders but higher scores in 5th graders. Letter shape may also play a role as a recent study [48] found that rounder letters yielded better reading fluency and were rated as more pleasant than angular letters by a group of children (4th-6th grade); however, comprehension was not impacted.…”
Section: Typography Research In Childrenmentioning
confidence: 97%